Analysis of Public Participation Levels in Paying Land and Building Taxes in 2020: (Case Study in Sukolilo Baru) - Nur Hanifah; Joko Suyono; Damarsari Ratnasahara Elisabeth (NAROTAMA UNIVERSITY, Indonesia, 2023)
This research was carried out to the community in Sukolilo Baru Village, Bulak District, Surabaya City. The purpose of this study is to find out how to increase community participation in paying land and building tax in Sukolilo Baru Village and to analyze what factors influence community participation in paying Land and Building Tax in Sukolilo Baru Village. To analyze the factors that influence community participation in paying land and building taxes in Sukolilo Baru Village, this study uses Slamet's theory which consists of several indicators, namely age level, education level, and employment and income levels. The data analysis used is a qualitative descriptive technique. The subjects in this study were determined based on the purposive sampling method. As well as those used as key informants. And collecting data with interview techniques and documentation with the community. The results of the study show that people's participation in paying land and building taxes in Sukolilo Baru Village is based on indicators of age , education, employment and income levels. The author's suggestion to increase community participation in paying land and building taxes is by giving awards to people who are obedient and obedient in paying land and building taxes, actively conducting counseling every year, and applying more and more to using proof of payment of paying taxes in managing all administration. in the village.